Reminescence of Radha Nadarajah : The first head school of Library Science, UiTM / Professor Dato' Dr. Raja Abdullah Yaacob - Yaacob, Raja Abdullah (Faculty of Information Management, 2009)
This is actually an exciting exercise for me when I was asked to recall what I remember about Mrs. Nadarajah, the first head of school of the then School of Library Science. Radha was a Singaporean who did LLB in Britain and also ended up doing ALA. When I asked her why she did not practice law, her answer was that she wanted to become a law librarian. I was thinking what a waste for a dynamic and eloquent person like her not to practice law. One thing we remembered about her is that, she took pride in her practical training in the British Board of Trade and all the time in the class she was giving that example. That is why I believe practical training is very crucial. At that time she made it a point to send students to do practical training almost every semester. This was made possible because at that time the number of students was very small.